2022
DOI: 10.1177/17534666221107313
|View full text |Cite
|
Sign up to set email alerts
|

Oral corticosteroid-sparing effects of mepolizumab in severe eosinophilic asthma: evidence from randomized controlled trials and real-world studies

Abstract: Oral corticosteroids (OCS) have long been a mainstay of treatment for asthma exacerbations and chronic severe asthma. However, it is increasingly recognized that both long-term and short-term OCS use are directly associated with a wide range of serious adverse effects, and as such OCS-sparing treatment alternatives are now widely recommended for patients with severe asthma. While several international guidelines recommend these treatments, guidance on OCS tapering, and which patients are most likely to tolerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Outside of this study, it has been shown that healthcare costs are higher in SCS versus non-SCS users, with the costs associated with SCS-related complications increasing with SCS dose [ 5 9 ]. When combined with the adverse effects associated with SCS use, the higher healthcare costs among SCS users may be a further supporting factor for the use of SCS-sparing medications, such as biologics, in patients with severe asthma [ 16 , 19 , 20 , 22 , 24 ]. Furthermore, the cost effectiveness of biologic treatments has been demonstrated in a number of studies, particularly when treatment is targeted to specific responder populations [ 27 , 28 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of this study, it has been shown that healthcare costs are higher in SCS versus non-SCS users, with the costs associated with SCS-related complications increasing with SCS dose [ 5 9 ]. When combined with the adverse effects associated with SCS use, the higher healthcare costs among SCS users may be a further supporting factor for the use of SCS-sparing medications, such as biologics, in patients with severe asthma [ 16 , 19 , 20 , 22 , 24 ]. Furthermore, the cost effectiveness of biologic treatments has been demonstrated in a number of studies, particularly when treatment is targeted to specific responder populations [ 27 , 28 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several biologic agents have been approved for the treatment of severe asthma, including omalizumab, reslizumab, tezepelumab, mepolizumab, benralizumab, and dupilumab [ 11 – 22 ]. These agents have demonstrated OCS-sparing effects both in clinical trials and in real-world settings [ 16 , 19 , 20 , 22 24 ]. While the cost effectiveness of biologics has been debated [ 25 ], and reductions in exacerbations requiring hospitalization are the primary driver of cost effectiveness with biologic therapy [ 26 , 27 ], chronic OCS reduction has also been reported to contribute to the lifetime discounted cost effectiveness of biologic therapy [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, biologics are recommended before chronic SGC in uncontrolled patients (72). Despite the proven reduction in exacerbation rates and SGC-sparing effects in real-life studies (73,74), biologics are still underprescribed in most regions in Spain (75,76).…”
Section: For Respiratory Eosinophilic Diseases: Crswnp and Sea-epmentioning
confidence: 99%